2014
DOI: 10.1371/journal.pone.0114521
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol Lipase Inhibitor JZL184 Improves Behavior and Neural Properties in Ts65Dn Mice, a Model of Down Syndrome

Abstract: Genetic alterations or pharmacological treatments affecting endocannabinoid signaling have profound effects on synaptic and neuronal properties and, under certain conditions, may improve higher brain functions. Down syndrome (DS), a developmental disorder caused by triplication of chromosome 21, is characterized by deficient cognition and inevitable development of the Alzheimer disease (AD) type pathology during aging. Here we used JZL184, a selective inhibitor of monoacylglycerol lipase (MAGL), to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 84 publications
(111 reference statements)
5
26
1
Order By: Relevance
“…However, increased number of entries at 11 months of age in Ts65Dn mice is close to statistical significance. Significant differences in the number of entries have been reported recently in aged Ts65Dn (Lysenko et al, 2014). However, our longitudinal study demonstrates that the number of entries for Ts65Dn animals remain similar at 2 and 11 months of age.…”
Section: Resultsmentioning
confidence: 87%
“…However, increased number of entries at 11 months of age in Ts65Dn mice is close to statistical significance. Significant differences in the number of entries have been reported recently in aged Ts65Dn (Lysenko et al, 2014). However, our longitudinal study demonstrates that the number of entries for Ts65Dn animals remain similar at 2 and 11 months of age.…”
Section: Resultsmentioning
confidence: 87%
“…Though we failed to detect an effect of increased Kcnj6 dose on working memory as examined in the Y-maze, we did observe normalization of exploratory behavior during Y-maze testing, suggesting that Kcnj6 dose may play a role in exploration in the context of this test. We note that deficient working memory has not responded to most of the treatments restoring long-term memory in genetic models of DS (Kleschevnikov et al, 2012a; Lysenko et al, 2014). A likely explanation is that the deficiency in working memory is genetically and mechanistically distinct from the deficits in long-term memory and synaptic plasticity, as studied herein.…”
Section: Discussionmentioning
confidence: 82%
“…To assess the impact of Kcnj6 dose on long-term memory, we used the novel object recognition test with a retention period of 24 h. In prior studies, this test consistently demonstrated impairment of long-term memory in Ts65Dn mice (Fernandez et al, 2007; Kleschevnikov et al, 2012a; Lysenko et al, 2014). On average, mice of all genotypes spent equal time investigating objects during both the acquisition ( p = 0.16–0.39) and testing ( p = 0.3–0.75; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated spontaneous locomotor activity was reported extensively in the Ts65Dn mice18313335127128. We analyzed the exploratory behavior and general locomotor activity in an open field arena.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated spontaneous locomotor activity has been documented both in young and old Ts65Dn mice18313335127128. Also in DS individuals, hyperkinetic and hyperactivity disorders are common158159.…”
Section: Discussionmentioning
confidence: 99%